La política del significado: discursos sociales sobre el abuso sexual de niños y su influencia en la iglesia católica - Demasure, Karlijn (Pelícano, 2019)
The Politics of Meaning: Societal Discourses on the Sexual Abuse of Children and Their Influence on the Catholic ChurchNota: Traducción del inglés al español a cargo de Diego Fonti. Texto original: Karlijn Demasure (2019). The Politics of Meaning. Societal Discourses on Sexual Abuse of Children and their Influence on the Catholic Church. In Vähäkangas A., Angel S., Helboe Johansen K., (eds.), The Politics of Space and Body. Reforming Practical Theology, International Academy of Practical Theology Conference Series (IAPT.CS), 1, 20-28. Disponible en https://doi.org/10.25785/ iapt.cs.v1i0.49ResumenEste artículo sobre el abuso sexual de niños contribuye a comprender el cambio del enfoque de los perpetradores que niega la voz de las víctimas, incluso al punto de considerar a las víctimas como delincuentes sexuales responsables por su abuso, a un enfoque de la víctimas primero. La iglesia católica ha sido fuertemente influida por los principales discursos en la sociedad que dan poder a los psiquiatras, terapeutas y trabajadores sociales. Sin embargo, con respecto al abuso clerical en la iglesia, se pueden identificar dos discursos distintos. En el primero, el pecado se considera causa del abuso, reduciéndolo a una cuestión de la voluntad. El segundo discurso considera que el abuso sexual infantil se debe al contexto de decadencia moral. Es importante por ello superarlos con una visión sistémica del tema.AbstractThis paper on child sexual abuse contributes to an understanding of the shift from a focus on perpetrators that denies the voice of the victims, even holding the victims to be sexual delinquents responsible for their abuse, to a victims first approach. The Catholic Church has been heavily influenced by the major discourses in society that give power to psychiatrists, therapists and social workers. However, with regard to clerical sexual abuse in the Church, two distinct discourses can be identified. In the first, sin is considered a cause for abuse, reducing it to a matter of the will. The second discourse considers child sexual abuse due to a context of moral decay. Both discourses need to be overcome by means of a sistemic view of the issue. Key words: Child Sexual Abuse, Catholic Church, Societal Discourses, Victims First Approach.